Interindividual variability in TPMT enzyme activity: 10 years of experience with thiopurine pharmacogenetics and therapeutic drug monitoring. (April 2014) - Chouchana, Laurent; Narjoz, Celine; Roche, Denis; Golmard, Jean-Louis; Pineau, Brigitte; Chatellier, Gilles; Beaune, Philippe; Loriot, Marie-Anne
Background & aims: TPMT activity and metabolite determination (6-thioguanine nucleotides [6-TGN] and 6-methylmercaptopurine nucleotides [6-MMPN]) remain controversial during thiopurine management. This study assessed associations between patient characteristics and TPMT activity, and their impact on metabolite levels.Patients & methods: A retrospective review of the laboratory database from a French university hospital identified 7360 patients referred for TPMT phenotype/genotype determination, and/or for 6-TGN/6-MMPN monitoring.Results: Four TPMT phenotypes were identified according to TPMT activity distribution: low, intermediate, normal/high and very high. Based on 6775 assays, 6-TGN concentrations were 1.6-fold higher in TPMT-deficient patients compared with TPMT-normal patients. Azathioprine dose and TPMT genotype were significant predictors of metabolite levels. Furthermore, 6-MMPN and 6-MMPN: 6-TGN ratios were, respectively, 1.6- and 2.2-fold higher in females than in males, despite similar TPMT, 6-TGN and azathioprine doses. An unfavorable ratio (≥20) was associated with a slightly higher TPMT activity.Conclusion: These results illustrate the usefulness of pharmacogenomics and metabolite measurement to improve the identification of noncompliance and patients at high risk for toxicity or therapeutic resistance. Original submitted 13 November 2013; Revision submitted 30 January 2014